Characteristics of EGFR Gene Mutation in Lung Adenocarcinoma at Adam Malik General Hospital - Novita Margaretta Ambarita; Noni Novisari Soeroso; Setia Putra Tarigan; Fotarisman Zalukhu (Jurnal Respirologi Indonesia, 2022)
Background: Epidermal growth factor (EGFR) is a transmembrane receptor that plays an important role in the development of cancer phenotypes. Some patients with lung cancer have genetic mutations. Several studies have found a close correlation of EGFR gene mutation with 15-20% of lung adenocarcinoma cases. This study aimed to determine the EGFR profile in adenocarcinoma lung cancer patients at Haji Adam Malik General Hospital.Methods: This was a prospective cohort study conducted at Haji Adam Malik General Hospital, Medan. This study used patients data for 3 years, starting from January 1, 2014 to D1ecember 31, 2016. The sample size in this study was 34 patients. The data were then analyzed using SPSS.Results: All patients were adenocarcinoma lung cancer patients with positive EGFR mutation. There were 9 subjects with EGFR mutation in exon 19; 11 subjects with exon 21 L858R mutation; and 3 subjects with exon 21 L861Q mutation. Meanwhile, there were 3 subjects with uncommon EGFR mutations, namely exon 18 mutation. Majority of subjects with exon 19 mutation were male, aged >60 years, smokers with mixed types of cigarettes and severe brinkmann index. In subjects with exon 21 L858R mutation, most of the patients were male, aged 50-60 years, smokers with mixed cigarette types and severe brinkmann index. The same characteristics were also observed in subjects with exon 18 mutation. However, for exon 21 L861Q mutation, the majority of subjects were female with varying ages, and were not smokers.Conclusion: Most of the study subjects profiles were male, aged over 60 years, smokers, with mixed types of cigarettes, and with severe Brinkman Index. The EGFR mutations most commonly occured in exon 21, followed by exon 19 (ins/del exon 19), exon 18, and a combination of 2 exons.